2021
DOI: 10.1007/s13399-021-01655-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of co-substrates’ mixing ratios and loading rate variations on food and agricultural wastes’ anaerobic co-digestion performance

Abstract: Tunisia is one of the developing countries which faces crucial challenges, the most prominent of which are the production of organic waste, the need for an appropriate waste treatment, and the demand for water and energy conservation. To this end, the present research was designed to develop a technical concept on closed cycle “biowaste to bioenergy” treating food waste (FW) through combined biological processes. In this approach, semi-continuous anaerobic co-digestion (ACoD) of FW, wheat straw (WS), and cattl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The major drawback of food waste digestion is the fast hydrolysis rate and the resulting drop in pH (<5.5) because of the accumulation of volatile fatty acids [80]. Therefore, co-digestion of food waste with stubborn feedstocks can help to retard the hydrolysis rate and reduce the VFAs [81]. El et al [81] co-digested agricultural waste, such as wheat straw and cow manure, with food waste in semi-continuous mesophilic AD and considered the effect of mixing ratio, C/N ratio, and variation of organic loading rates from 2 to 3.6 kg VS/m 3 d on the digester performance.…”
Section: Biogas Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The major drawback of food waste digestion is the fast hydrolysis rate and the resulting drop in pH (<5.5) because of the accumulation of volatile fatty acids [80]. Therefore, co-digestion of food waste with stubborn feedstocks can help to retard the hydrolysis rate and reduce the VFAs [81]. El et al [81] co-digested agricultural waste, such as wheat straw and cow manure, with food waste in semi-continuous mesophilic AD and considered the effect of mixing ratio, C/N ratio, and variation of organic loading rates from 2 to 3.6 kg VS/m 3 d on the digester performance.…”
Section: Biogas Yieldmentioning
confidence: 99%
“…Therefore, co-digestion of food waste with stubborn feedstocks can help to retard the hydrolysis rate and reduce the VFAs [81]. El et al [81] co-digested agricultural waste, such as wheat straw and cow manure, with food waste in semi-continuous mesophilic AD and considered the effect of mixing ratio, C/N ratio, and variation of organic loading rates from 2 to 3.6 kg VS/m 3 d on the digester performance. The result demonstrated that the highest biogas yield increased by 119.97% for the organic load of 3.6 kg VS/m 3 d fed with the optimum mixing ratio of FW:CM (75:25) and a C/N ratio of 20.03.…”
Section: Biogas Yieldmentioning
confidence: 99%
“…In fact, the feasibility of anaerobic treatments depends significantly on the effectiveness of end-products uses. Therefore, to unlock the sustainability of anaerobic process, digestate-uses gain progressively attention [35]. To this end, the current research work investigated whether the generated AD-effluent met the required criteria to be efficiently exploited for agricultural purposes.…”
Section: Criteria For Digestate Selectionmentioning
confidence: 99%